1998
DOI: 10.1002/jor.1100160606
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts are required for bone tumors to grow and destroy bone

Abstract: It has been hypothesized that bone resorption during tumor osteolysis is performed by osteoclasts. Data supporting this hypothesis have been provided from analysis of human biopsy specimens obtained from sites of tumor osteolysis, as well as from experimentation with in vivo animal models. Experiments in this report take this concept one step further by testing the hypothesis that osteoclasts are required for bone tumors to grow and destroy bone. To test this hypothesis, the influence of an osteolytic sarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…This finding is of interest with regard to the pathogenesis of tumour osteolysis in breast cancer as, in addition to an increase in osteoclast number, a prominent macrophage infiltrate is commonly found in metastatic breast carcinomas (Bugelski et al, 1987;Van Ravenswaay Claasen et al, 1992). Moreover, osteoclasts are required for growth of breast cancer metastases in bone and tumour osteolysis involves recruitment of osteoclast precursors and activation of mature osteoclasts (Clohisy et al, 1996a(Clohisy et al, , 1996bClohisy and Ramnaraine, 1998).In this study, our aim has been to analyse the cellular mechanisms of bone resorption in breast cancer. As TAMs in metastases of breast cancer are derived from circulating monocytes (Mantovani et al, 1992), we have sought to determine whether the Summary The cellular mechanisms that account for the increase in osteoclast numbers and bone resorption in skeletal breast cancer metastasis are unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is of interest with regard to the pathogenesis of tumour osteolysis in breast cancer as, in addition to an increase in osteoclast number, a prominent macrophage infiltrate is commonly found in metastatic breast carcinomas (Bugelski et al, 1987;Van Ravenswaay Claasen et al, 1992). Moreover, osteoclasts are required for growth of breast cancer metastases in bone and tumour osteolysis involves recruitment of osteoclast precursors and activation of mature osteoclasts (Clohisy et al, 1996a(Clohisy et al, , 1996bClohisy and Ramnaraine, 1998).In this study, our aim has been to analyse the cellular mechanisms of bone resorption in breast cancer. As TAMs in metastases of breast cancer are derived from circulating monocytes (Mantovani et al, 1992), we have sought to determine whether the Summary The cellular mechanisms that account for the increase in osteoclast numbers and bone resorption in skeletal breast cancer metastasis are unclear.…”
mentioning
confidence: 99%
“…This finding is of interest with regard to the pathogenesis of tumour osteolysis in breast cancer as, in addition to an increase in osteoclast number, a prominent macrophage infiltrate is commonly found in metastatic breast carcinomas (Bugelski et al, 1987;Van Ravenswaay Claasen et al, 1992). Moreover, osteoclasts are required for growth of breast cancer metastases in bone and tumour osteolysis involves recruitment of osteoclast precursors and activation of mature osteoclasts (Clohisy et al, 1996a(Clohisy et al, , 1996bClohisy and Ramnaraine, 1998).…”
mentioning
confidence: 99%
“…101,104 Because osteoclast activity is crucial for bone resorption, 28,101,104 if osteoclast activity causing bone destruction could be inhibited, cancer-induced pain might be relieved. 30,60,69,70,164 On the basis of this concept, several investigators demonstrated that they could administer the novel analgesic osteoprotegerin ligand and successfully treat cancer pain in male C3H/HeJ mice. 69 Osteoprotegerin ligand is a member of the tumor necrosis factor family and blocks osteoclast activity that causes cancer-induced bone destruction.…”
Section: Models Of Cancer Painmentioning
confidence: 99%
“…Upon activation, osteoclasts have been shown to cause cancer-induced osteolysis in bone [Clohisy and Ramnaraine, 1998]. Novel experimental models allow osteolytic bone destruction to be correlated to pain behaviors, neurochemical changes, and cellular reorganization of the spinal cord [Hukkanen et al, 1992;Honore et al, 2002;Sevcik et al, 2004].…”
Section: Animal Models Of Bone Cancer Painmentioning
confidence: 99%